2015
DOI: 10.1155/2015/712683
|View full text |Cite|
|
Sign up to set email alerts
|

Herbal Mouthwash Containing Extracts of Baccharis dracunculifolia as Agent for the Control of Biofilm: Clinical Evaluation in Humans

Abstract: Baccharis dracunculifolia DC (Asteraceae), popularly known as “alecrim-do-campo,” is largely distributed in South America, is shown to exhibit protective actions against gastric ulcers, has anti-inflammatory properties, and is hepatoprotective. Several essential oils obtained from Baccharis species possess biological activities, such as antimicrobial and antivirus activities. This randomized controlled trial evaluated the efficacy of B. dracunculifolia in the reduction of dental biofilm, comparing this natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 43 publications
0
15
0
3
Order By: Relevance
“…Some of the 14.29% of the studies that had negative results based on the conventional significance level 0.05 tended to present the results in a positive light. For instance, one study that found no significant difference among four groups (p = 0.602), of which two had received active controls, one the test product and one a placebo product concluded that "B. dracunculifolia had the same efficiency of the materials used to oral hygiene in reduction of dental plaque and, consequently, prevention of dental caries" [86]. A more likely conclusion in this case would be that the study did not have sufficient power to discriminate between the active interventions and placebo.…”
Section: Clinical Trial Resultsmentioning
confidence: 99%
“…Some of the 14.29% of the studies that had negative results based on the conventional significance level 0.05 tended to present the results in a positive light. For instance, one study that found no significant difference among four groups (p = 0.602), of which two had received active controls, one the test product and one a placebo product concluded that "B. dracunculifolia had the same efficiency of the materials used to oral hygiene in reduction of dental plaque and, consequently, prevention of dental caries" [86]. A more likely conclusion in this case would be that the study did not have sufficient power to discriminate between the active interventions and placebo.…”
Section: Clinical Trial Resultsmentioning
confidence: 99%
“…Some of the 14.29% of the studies that had negative results based on the conventional significance level 0.05 tended to present the results in a positive light. For instance, one study that found no significant difference among four groups (p=0.602), of which two had received active controls, one the test product and one a placebo product concluded that "B. dracunculifolia had the same efficiency of the materials used to oral hygiene in reduction of dental plaque and, consequently, prevention of dental caries" [78]. A more likely conclusion in this case would be that the study did not have sufficient power to discriminate between the active interventions and placebo.…”
Section: Clinical Trial Resultsmentioning
confidence: 99%
“…Baccharis dracunculifolia is a plant native to Brazil popularly known as field rosemary-of-field [24]. This species has been recognized for its diverse pharmacological properties, such as antifungal [25], anticarcinogenic [26,27], antimicrobial [28,29], antioxidant [30], antileishmanial and antiplasmodial [31] as a tick insecticide [32], and as an insecticide and repellent [33]. It is traditionally used for the treatment of liver problems and inflammation.…”
Section: Introductionmentioning
confidence: 99%